A comparative experimental investigation of torque capabilities induced by conventional and active, passive self-ligating brackets - Katsikogianni, Eleni (European journal of orthodontics, 2015)
A proper selected bracket-archwire combination displays a determining factor in the efficacy of torque applied to a tooth at the final st
Advance access publication 20 November 2014
Gesehen am 02.07.2020